Is rainfall seasonality important for reproductive strategies in viviparous Neotropical pit vipers? A case study with Bothrops leucurus from the Brazilian Atlantic Forest - Barros, Veronica Alberto [UNESP]; Rojas, Claudio Augusto; Almeida-Santos, Selma Maria [UNESP] (British Herpetol Soc, 2014)
Two populations of the Neotropical lancehead Bothrops leucurus were studied in two locations in Brazil (Espirito Santo, ES, and Bahia, BA) with different rainfall seasonality patterns. The timing of reproduction was very similar in both populations, with the mating season occurring in autumn (when spermatozoa were found in uteri) and births occurring in summer. In males, spermatogenesis peaked in autumn, with evidence for increased secretory activity in the epithelium of the ductus deferens during the mating season in both populations. Our results indicate that phylogenetic inertia plays a major role in determining the timing of reproductive events in B. leucurus. However, snout-vent length (SVL) and clutch size were larger in individuals from BA than ES, which may be a result of differences in rainfall seasonality or other proximate factors (e.g., differential prey availability).
Keywords: clutch size; environmental conditions; long-term sperm storage; phylogenetic inertia; reproductive cycles; spermatogenesis